Eclipta alba (Bhringraj): Potential Natural Anthelmintic Drug against Pheretima posthuma - Sujata R. Khatal; Machindra J. Chavan; Dipak N. Raut (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
Eclipta alba is the traditional medicine widely used for the treatment of gastrointestinal disorders, respiratory tract disorders (including asthma), fever, hair loss and graying of hair, liver disorders (including jaundice), skin disorders, spleen enlargement, and cuts and wounds. It is also proven as an effective anticancer, hepatoprotective, snake venom neutralizing, anti-inflammatory, and antimicrobial drug. The main phytoconstituents like wedelolactone, ecliptalbine luteolin, ursolic acid, oleanolic acids and apigenin has formed a basis of new drugs against cancer, arthritis, gastrointestinal disorders, skin diseases, and liver disorders. The present study was carried out to investigate the anthelmintic potential of methanolic extract of the whole plant of Eclipta alba (L.) Hassk against Pheretima posthuma as a species of earthworm. Various concentrations (25-100 mg/ml) of methanolic extract were evaluated for anthelmintic activity by recording the time required for paralysis and death of worms. Albendazole was used as standard. The result indicates that methanol extracts significantly (p<0.01) exhibited paralysis at lower doses of 50, 75 and 100 mg/ml and caused death of worms at doses of concentrations 75 and 100 mg/ml when compared with standard.